EVALUATION OF A NOVEL, NATURAL LOCUST BEAN GUM AS A SUSTAINED RELEASE AND MUCOADHESIVE COMPONENT OF TIZANIDINE HYDROCHLORIDE BUCCAL TABLETS - V, HARIKRISHNAN; S, MADHUSUDHAN; A, SANTHIAGU (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Mucoadhesive polymers that bind to the gastric mucins or epithelial cell surface are useful in drug delivery for the purpose of increasing the intimacy andduration of contact of the drug with the absorbing membrane. Mainly synthetic polymers are in use for this purpose. Probably the biodegradability of thesynthetic polymers is questionable. In the present work mucoadhesive buccal tablets of tizanidine hydrochloride were prepared using locust bean gumthat has better mucoadhesive property than synthetic polymer. The in vitro adhesive and mucoadhesive strength and swelling property of mucoadhesivmaterial locust bean gum were evaluated by Share Stress and Park and Robinson methods. Buccal formulations of tizanidine hydrochloride tablets werprepared using locust bean gum, and thickness, hardness, friability, weight variation, and assay of tablets were tested. The in vitro drug release studof tizanidine hydrochloride exhibited extended drug release profile for tablets prepared. Higuchi and Peppas data reveal that the drug released by nonFickian diffusion mechanism. The present study shows that formulation containing 50% locust bean gum have greater mucoadhesive property than allother formulation. Increase in concentration of locust bean gum increases in the bioadhesive strength and swelling ratio in the 50 mg of locust bean gum. Keywords: Mucoadhesive, Tizanidine hydrochloride, Tablets, Locust bean gum.